Analisis Relasi Gender pada Praktik Baik Percepatan Penurunan Stunting di Kabupaten Labuhanbatu Utara - Khairani, Leylia (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Provinsi Sumatera Utara, 2024)
This study aims to analyze the role of gender relations in best practices for accelerating the reduction of stunting in Labuhanbatu Utara Regency. Stunting, characterized by impaired child growth due to chronic malnutrition, remains a serious health issue in Indonesia. Although the prevalence of stunting has decreased, gender relations within families—particularly regarding child-rearing and nutrition—have yet to receive optimal attention in stunting reduction programs. This research employs a qualitative method with a case study approach conducted in Aek Korsik Village, which has achieved the status of a zero-stunting village. Data were collected through in-depth interviews with pregnant women, mothers with young children, prospective brides, and Family Assistance Team (TPK) cadres. The findings reveal that family roles are still predominantly assigned to women, especially mothers, who bear the primary responsibility for child-rearing and managing nutritional needs. Mothers play a central role in routine activities such as preparing meals and exclusively breastfeeding, while the involvement of fathers is more limited to important decision-making, particularly concerning the child's health. However, decisions like when to take a child to the doctor are typically made jointly by both husband and wife, indicating progress toward gender equality. Additionally, extended family support, especially from parents and in-laws, significantly helps mothers fulfill their caregiving responsibilities. Although traditional norms still influence the division of roles within the family, there are indications of movement toward greater gender equality, particularly in joint decision-making related to family health.